2012 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology 2012
DOI: 10.1109/wi-iat.2012.188
|View full text |Cite
|
Sign up to set email alerts
|

Database Keyword Search: A Perspective from Optimization

Abstract: Optimization-related techniques are playing ever increasing role for Web intelligence. Yet optimization may mean different things to different people. In this paper, starting with a general discussion on the many facets of optimization in information technology (IT), we focus our examination on the recent development in database keyword search, from an optimization-oriented perspective. We first present a review and analysis on related literature, pointing out the need for incorporating contextual information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The task is to understand and represent the given natural language query in its equivalent SQL format. Authors from [6], [7] demonstrated how the KWS systems give more accurate results by giving particular importance to logical operators (and, or, not); similarly, [8] focused on words such as 'average, count, total' etc., to deal with advanced NLP queries. However, such attempts were limited in scope and domain, as the set of words to focus upon was domain specific.…”
Section: Regular Expressionsmentioning
confidence: 99%
“…The task is to understand and represent the given natural language query in its equivalent SQL format. Authors from [6], [7] demonstrated how the KWS systems give more accurate results by giving particular importance to logical operators (and, or, not); similarly, [8] focused on words such as 'average, count, total' etc., to deal with advanced NLP queries. However, such attempts were limited in scope and domain, as the set of words to focus upon was domain specific.…”
Section: Regular Expressionsmentioning
confidence: 99%